Correlation between intracellular heat shock protein 70 expression and cervical lymph nodes enlargement in nasopharyngeal carcinoma - Romdhoni, Achmad C; Herawati, Sri; Mustikaningtyas, Elida (Folia Medica Indonesiana, 2017)
Tumor growth and metastasis in NPC patients suspected role of several molecular biomarkers that have been identified in tumor specimens of patients with NPC. Recent research states intracellular Hsp70 is a stress protein that is a main factor for the growth, invasion and metastasis of NPC. The purpose of this study is to analyze intracellular Hsp70 protein expression of NPC patients which correlate with staging of NPC as clinical manifestation. This study used cross sectional design. In this study, formalin-fixed paraffin-embedded biopsy specimens were obtained from 18 NPCs with all of histopathology and clinically divided into N0, N1, N2, N3. The expression of intracellular Hsp70 was obtained with immunohistochemistry using monoclonal antibody Anti Human Hsp70 antibodi from Santa Cruz Biotechnology, California, USA. Assessment of the staining was performed with Remmele methode by Histopathologies doctor Consultant. The Spearman's test was used to determine the relationship between expression of intracellular Hsp70 protein and enlargement cervical nodul of NPC. Statistical significance was defined as p <0,05. There were 18 patients NPC patients that met the inclusion and exclusion criteria. Showed negative intracellular Hsp70 expression by 16,67% for all sample in which consist 1 patient of N0, 1 patient of N1, 1 patient of N2, 0 patient of N3. Followed by 27,78% mild positive intracellular Hsp70 expression which consist 0 patient of N0, 2 patients of N1, 0 patient of N2, 3 patients of N3. Followed by 44,44% moderate positive intracellular Hsp70 expression which consist 0 patient of N0, 0 patient of N1, 1 patient of N2, 9 patients of N3. Followed by 11,11% strongly positive intracellular Hsp70 expression which consist 0 patient of N0, 0 patient of N1, 0 patient of N2, 2 patients of N3. Spearman test results test scores p = 0.01 with a correlation coefficient 0.606. Correlation of intracellular Hsp70 protein expression with enlargement cervical nodul of lymphe (N0, N1, N2, N3) in patients with NPC showed significant (p<0.05). In conclusion, there was correlation between increase of the intacellular Hsp70 expression and enlargement cervical nodul of lymphe in nasopharyngeal carcinoma.